CREDITOR OF FIDUCIARY FACING BANKRUPTCY, WHAT SHOULD THEY DO? - Ningsih, Ayup Suran (Diponegoro Law Review, 2025)
This study investigates the legal framework surrounding fiduciary guarantees in Indonesia, elucidates the position of secured creditors when debtors face bankruptcy, and scrutinizes the procedural regulations for enforcing fiduciary liens in the aftermath of bankruptcy proceedings. The research utilizes a normative legal methodology and an analytical-descriptive approach, referencing foundational doctrines in the Civil Code and the provisions of Law No. 37 of 2004 regarding the Suspension of Debt Payment Obligations and Bankruptcy. Data were gathered from primary legal texts, particularly Law No. 42 of 1999 on Fiduciary Guarantees. They were further supported by secondary literature in legal scholarship and relevant non-legal sources that provide insights into practical enforcement trends. The examination starts by delineating the legal framework of fiduciary security: identifying qualifying collateral (including movable and specific immovable assets), specifying registration and perfection criteria, and differentiating fiduciary liens from traditional pledges and mortgages. The focus then shifts to the point of insolvency, examining the classification of fiduciary creditors within the bankruptcy hierarchy—distinguished as preferred or concurrent claimants—and the rights they maintain to identify and reclaim collateral beyond the general estate. The study delineates the procedural steps required by Law No. 37/2004 for post-bankruptcy enforcement, encompassing notice provisions, valuation, auction sale, and distribution of proceeds. The findings indicate that Indonesian law establishes a structured framework for fiduciary guarantees; however, there are notable tensions between the insolvency moratorium and the secured creditor’s entitlement to timely enforcement. Furthermore, instances of priority conflicts can emerge in practice, highlighting the necessity for more explicit guidelines regarding the ranking of creditor claims. This study integrates doctrinal theory, statutory text, and procedural detail to provide a thorough reference for practitioners and policymakers. It proposes specific reforms to enhance predictability and boost creditor confidence in Indonesia’s secured lending framework.